CFD and Experimental Analysis of a Falling Film outside Smooth and Helically Grooved Tubes - Onan, Cenk; Ozkan, Derya Burcu; Erdem, Serkan (SAGE PUBLICATIONS LTD, 2014)
Simultaneous heat and mass transfer are investigated in a falling film outside grooved and smooth tubes. A numerical analysis of the helically trapezoidal-grooved and reference smooth tube was performed in the computational fluid dynamics program Ansys Fluent 14. The three-dimensional model drawings in the x, y, and z coordinates are used, and the effects of the falling film outside the helically grooved tube on the surface temperature and surface heat transfer coefficient are determined. The average surface temperature, heat transfer coefficient, and Nu values are determined experimentally for a constant heat flux. An uncertainty analysis and Nu correlation for the grooved tube are also provided in this study. The Reynolds number varied between 50 and 350 for the falling film and between 1500 and 3500 for air. Using a computational fluid dynamics (CFD) analysis for the reference smooth tube, the experimental results are validated within 2-12% difference. The experimental results are also within 6-13% of the grooved tubes.
Keywords: HEAT-TRANSFER; EVAPORATION; TRANSITIONS; Thermodynamics; Engineering